The Impact of Using Different Ratios of Latex Rubber on the Characteristics of Mortars Made with GGBS and Portland Cement. Issue 1 (March 2021) - Al-Khafaji, Zainab S.; Falah, Mayadah W.; Shubbar, Ali A.; Nasr, Mohammed Salah; Al-Mamoori, Shahad F.; Alkhayyat, Ahmed; Al-Rifaie, Ali; Eissa, Abdulhadi; Al-Mufti, Rafal Latif; Hashim, Khalid
Abstract: Preserving natural resources and implementing the concepts of sustainable engineering to approach the zero waste concept helped in reducing the detrimental environmental effects in the last two-decade. Proposed re-using of Ground Granulated Blast Furnace Slag (GGBS) as an alternate solution is to get rid of them and profit from them concurrently. In this process, GGBS is used as cement substitute material to enhance mortar characteristics. On the other hand, the required water for concrete mixture should be characterized by several characters, which similar to drinkable water, therefore, using of Latex Rubber as a water substitution reduces the demand for such water in the construction industry. In this project, percentages of GGBS that have been used were 0%, 10%, 30%, and 50% which compatible with (0, 10, 20 and 30) % of Latex Rubber. Suitable tests were performed to measure properties of mortar by GGBS and Latex Rubber such as setting time, compressive strength and Permeability test (Electrical resistivity). The results obtained indicate that the setting time reduced with increasing Rubber Latex in spite of increasing the proportion of water to binder. Additionally, increasing the Latex Rubber amount leads to decrease the compressive strength and electrical resistivity of mortars.